Dolphins and sharks - Tyler, James Anthony (Oberon modern plays., 2017)
Dolphins and Sharks follows three employees of Harlem Office, New York, a neighbourhood copy shop where promotions are rare, raises are even rarer, and racism is often on display. But when one staff member is given the chance to move up to manager, friendships are tested and loyalty turns out to be less valuable than cold hard cash. Soon cutbacks and office politics have everyone fighting to keep their jobs and their sanity. A searing new comedy about clocking in, clocking out and rising up.